COVID-19: Pathophysiology, treatment options, nanotechnology approaches, and research agenda to combating the SARS-CoV2 pandemic (2020)
The recent corona virus disease (COVID-19) outbreak has claimed the lives of many around the world and highlighted an urgent need for experimental strategies to prevent, treat and eradicate the virus. COVID-19, an infectious disease caused by a novel corona virus and no approved specific treatment is available yet. A vast number of promising antiviral treatments involving nanotechnology are currently under investigation to aid in the development of COVID-19 drug delivery. The prospective treatment options integrating the ever-expanding field of nanotechnology have been compiled, with the objective to show that these can be potentially developed for COVID-19 treatment. This review summarized the current state of knowledge, research priorities regarding the pandemic and post COVID-19. We also focus on the possible nanotechnology approaches that have proven to be successful against other viruses and the research agenda to combat COVID-19.